2014
DOI: 10.1186/1471-2318-14-59
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of perceived environmental barriers and disability in community-dwelling elderly in Taiwan – a population-based study

Abstract: BackgroundTo identify the relationship between perceived environmental barriers and disability in community-dwelling elderly.MethodsCross-sectional study in two community service centers in Tainan. We enrolled 200 community-dwelling residents, aged above 65 years, who had resided in the same community for at least 12 months. Basic activity of daily living (BADL) and instrumental activity of daily living (IADL) were assessed using the Hierarchy of Care Required (HCR). There were 59 participants in BADL disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
2
5
0
2
Order By: Relevance
“…One of the study's findings revealed that some of the disability-related factors (type, severity, cause, need for assistance, and use of devices) were more strongly associated with the perception of environmental barriers outside the home environment. This last finding corroborates those of previous studies, in which physical limitations (self-care and mobility) and the degree of disability were associated with a greater perception of environmental barriers 24 , 26 , 27 .…”
Section: Discussionsupporting
confidence: 92%
“…One of the study's findings revealed that some of the disability-related factors (type, severity, cause, need for assistance, and use of devices) were more strongly associated with the perception of environmental barriers outside the home environment. This last finding corroborates those of previous studies, in which physical limitations (self-care and mobility) and the degree of disability were associated with a greater perception of environmental barriers 24 , 26 , 27 .…”
Section: Discussionsupporting
confidence: 92%
“…Lien et al 30 associated the perception of environmental physical barriers with disability in basic and instrumental activities of daily living among elderly Thai people. Zhang et al 31 , assessing CVA survivors in rural China, found an association between physical barriers and limitations in performing activities and restrictions in participation.…”
Section: Discussionmentioning
confidence: 99%
“…Para diagnosticar as barreiras que dificultam a prática regular de AF por parte do idoso, foi adaptado por Hirayama (2005) Outras barreiras, ainda, incluem falta de acesso a locais apropriados, à distância ou à falta de transporte (Flauskerud, & Nyamathi, 2000), mas que, observa-se não ser fator preponderante no presente estudo. As criações de espaços públicos destinados para esta prática são opções que já existem em algumas localidades; no entanto, muitos municípios ainda não dispõem de tais equipamentos, sendo um viés para a facilitação de espaços adequados para a AF (Lien, Guo, Chang, Lin, & Kuan, 2014). Ademais, a motivação para o deslocamento destas pessoas é outro fator que pondera sobre essa atitude (Lien, et al, 2014).…”
Section: Procedimentos Metodológicosunclassified
“…As criações de espaços públicos destinados para esta prática são opções que já existem em algumas localidades; no entanto, muitos municípios ainda não dispõem de tais equipamentos, sendo um viés para a facilitação de espaços adequados para a AF (Lien, Guo, Chang, Lin, & Kuan, 2014). Ademais, a motivação para o deslocamento destas pessoas é outro fator que pondera sobre essa atitude (Lien, et al, 2014).…”
Section: Procedimentos Metodológicosunclassified